Pengalaman Keterbukaan Diri Dalam Aplikasi Anonim pada Pengguna Tell - Viendiyani, Eka; Nursanti, Siti; Lubis, Fardiah Oktariani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to reveal the communication experience behind self-disclosure by Tell users through an anonymous application. This study uses a qualitative method with a phenomenological approach to describe the research problem. The results of the study showed that the communication experiences experienced by the informants included making new friends, being anonymous, making them comfortable, being free to tell stories, being a place for self-disclosure and venting all emotions and helping to find solutions. Then also have positive and negative experiences. The meaning of anonymous self-disclosure in Tell for informants is as a safe place to express self-problems and a comfortable, non-boring anonymous place that can only be conveyed in Tell, relieve feelings and emotions, and get solutions and assistance. The motives that prompted the informants to open themselves anonymously at Tell were divided into motives because of curiosity, relief of feelings and as a place for discussion and a place to hide influenced by their past experiences, but there were in order motives that were oriented towards the goal of opening up anonymous self that they want to achieve. Keywords: communication experience, anonymous self disclosure, phenomenology, tell